Comparison of OMI-DOAS total ozone column with ground-based measurements in Argentina - P. F. Orte; E. Luccini; E. Wolfram; F. Nollas; J. Pallotta; R. D'Elia; G. Carbajal; N. Mbatha; N. Hlongwane (Revista de Teledetección)
Total ozone column (TOC) measurements through the Ozone Monitoring Instrument (OMI/NASA EOSAura) are compared with ground-based observations made using Dobson and SAOZ instruments for the period 2004–2019 and 2008–02/2020, respectively. The OMI data were inverted using the Differential Optical Absorption Spectroscopy algorithm (overpass OMI-DOAS). The four ground-based sites used for the analysis are located in subpolar and subtropical latitudes spanning from 34°S to 54°S in the Southern Hemisphere, in the Argentine cities of Buenos Aires (34.58°S, 58.36°W; 25 m a.s.l.), Comodoro Rivadavia (45.86°S, 67.50°W; 46 m a.s.l.), Río Gallegos (51.60°S, 69.30°W; 72 m a.s.l.) and Ushuaia (54.80°S, 68.30°W; 14 m a.s.l.). The linear regression analyzes showed correlation values greater than 0.90 for all sites. The OMI measurements revealed an overestimation of less than 4 % with respect to the Dobson instruments, while the comparison with the SAOZ instrument presented a very low underestimation of less than 1 %.